Dual‐Band Double‐Cylindrical‐Ring 3D Frequency Selective Surface. Issue 1 (1st February 2017) - Can, Sultan; Karakaya, Emrullah; Bagci, Fulya; Yilmaz, Asim Egemen; Akaoglu, Barıs
Abstract : This study presents a dual‐band 3D frequency selective surface that provides a large degree of freedom in frequency and bandwidth adjustability. The proposed structure is evaluated in terms of its structural parameters, and prototypes are fabricated. The radius of the copper rings and the height of the cylinders are considered, and are shown through full‐wave electromagnetic simulations to have a significant effect on the frequency characteristics of the frequency selective surface. The measurement results of the fabricated samples are compared with the simulation results, and a satisfactory agreement is obtained.